Progress report from the AMAP Board to the SAO Meeting in Reykjavik, Iceland, April 9-10, 2003. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2003)
"AMAP is following the approved work plan for the period 2003-2004 as outlined in the SAO report to Ministers, Ivalo 2002. The main task for AMAP during this period is to produce the ACIA scientific assessment and policy reports, to be presented to the Ministerial meeting in 2004. This is a joint work with CAFF and IASC. When the SAO meeting takes place a scientific cross-fertilization meeting will have been arranged in Durham, New Hampshire in USA, and back to back to this meeting a scoping workshop for the policy paper will be arranged. Report from these two events and any specific requests to the SAOs arising from the meetings, e.g. how to finance to production/printing of the ACIA reports, how to disseminate the results in a best way etc., will be presented at the SAO meeting." /./